FORMULASI DAN KARAKTERISASI MIKROEMULGEL ETIL P-METOKSISINAMAT (EPMS) DARI RIMPANG KENCUR (Kaempferia galanga Linn) - Sriarumtias, Framesti Frisma; Mahendra Rizkio Syamsudin, Raden Aldizal; Ummah, Liyatul; Abdillah, Fajar Fauzi (Jurnal Kefarmasian Akfarindo, 2022)
Ethyl p-methoxycinnamate (EPMC) is the main compound from the rhizome of kencur (Kaempferia galanga Linn) isolated with a non-polar solvent, n-hexane. Several studies have proven that EPMC has a pharmacological effect as an anti-inflammatory. The purpose of this study was to make a topical formulation of EPMC using microemulgel preparations. The method used in the manufacture of microemulsions is to make a spontaneous microemulsion system and load it into a gel base. The oil phase used is isopropyl myristate, the surfactant used is tween 80, cosurfactant ethanol 96%, gelling agent is carpopol 340, triethanolamine (TEA) as a base and propylene glycol as a humectant. The dose of EPMC used was 200 g/mL. Four microemulgel formulations have been made, namely B1, B2, B3 and B4 with various concentrations of surfactant and cosurfactant. The results showed that the best formula was B3 formula with 5% isopropyl myristate, 40% Tween 80, 10% ethanol 96%, 10% propylene glycol, 1% carbopol, TEA and aquades. The conclusion of this formula is that the use of surfactants and cosurfactants in large quantities makes a transparent appearance and better stability than other formulations.